Navigating ICT Challenges and Effects at Rekopantswe Senior Phase Schools: Exploring Teaching and Learning Results - Mokgadi, Thapelo; Moloi, Tshepang Jacob (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The effective and sustained use of Information and Communication Technologies (ICTs) is critical to meeting 21st century educational demands. ICT integration is no longer merely an enhancement but a fundamental shift that requires active participation from teachers and school management. Despite its potential, ICT adoption in South African schools remains inconsistent, with full-scale integration occurring only after 1994. The integration process is largely affected by challenges such as inadequate teacher training, limited infrastructure, negative attitudes, and insufficient technical support, which hinder sustainable implementation. These challenges affect schools in under-resourced areas, such as those in the Rekopantswe sub-district, where ICT implementation remains inadequate. This study focuses on a critical research gap, exploring the unique challenges impeding integration in senior phase classrooms within the sub-district. A qualitative research approach is employed, using semi-structured interviews, classroom observations, and group discussions with senior-phase teachers and learners in Rekopantswe sub-district schools. Findings reveal that while teachers recognize ICT’s pedagogical benefits, its effective integration is constrained by a lack of formal training, technical resources, and inconsistent institutional support. The study underscores the need for structured professional development programs designed to the contextual needs of teachers and improved infrastructural support to enhance ICT‘s impact on teaching and learning. Through reflections on the barriers, the study adds to the body of knowledge by highlighting strategies to be adopted in fostering ICT integration in less resourced schools, informing policy direction and future research in the field.